Case study of mental skills training for a taekwondo Olympian - Lim, T. H.; O`Sullivan, D. M. (Journal of Human Kinetics, 2016)
The purpose of this study was to identify the effect of systematic mental skills training (MST) for a taekwondo gold medallist. Based on MST of other sports, this programme was designed for a single subject who competed in the Olympics. The Korean test of performance strategies, Sport Attributional Style in Korean Athletes, and a few sessions of interviews were applied to investigate the effect of MST. The pre and post-test mean scores of both the Korean test of performance strategies and Sport Attributional Style in Korean Athletes were compared. Interviews recorded the athlete`s psychological characteristics. Excluding the `activation` variable, all of the psychological skills, e.g. self-talk (4.25-5), emotional control (3.75-4.5), automaticity (3.75-4.25), goal setting (4.5-5), imagery (4.25-5), negative thinking (3.25-4.75), anxiety management (4.5-5), and physical and mental condition (4.5-5) improved. MST is believed to have helped the athlete succeed.